Media management on journalists, for example, Khabat newspaper - Ahmad, Asst.L.ayad Ahmad Murad (Sulaimani Journal for Humanities, 2025)
This research is entitled (The role of media management on journalists, for example, Khabat newspaper). It is a descriptive study conducted in a graphical manner. In order to achieve the researcher's objectives, he relied on the graphic form. The subject of this study is journalists in the Kurdistan Region and the subject of the study is the staff members of the newspaper (Khabat) who are all artists, reporters, typists, etc. (34) forms were distributed and necessary responses were received. The study is a scientific attempt to demonstrate the role of management in the institution. It also demonstrates the type of role and how it has a positive impact on members of the media organization. This research is a descriptive research, in which the method of media surveying is used, which helps the researcher to highlight the phenomenon he is investigating, and is a realistic attempt to understand the facts. The most important results: The results of this study show that the editorial board of Khabat newspaper helps its journalists without discrimination. Most of the respondents have a bachelor's degree, as shown in Table 4 . It turns out that the newspaper's editorial board, which is active from the top to the bottom of the pyramid. Because the newspaper is a party newspaper, most of its members (the research sample) support the party's policies and programs.
Keywords: Role; Administration; Media; Journalists; Khabat Newspaper